A TREATISE ON THE AMICABLE NUMBERS 220 AND 284 ATTRIBUTED TO ABŪ MA'SHAR AL-BALKHĪ - Matar, Zeina (Journal of Semitic studies, 1990)
ZEINA MATAR, OLIVER KAHL; A TREATISE ON THE AMICABLE NUMBERS 220 AND 284 ATTRIBUTED TO ABŪ MA'SHAR AL-BALKHĪ, Journal of Semitic Studies, Volume XXXV, Issue 2,